Upaya Peningkatan Kepuasan Kerja Guru SMK Islam Miftahul Huda Berbasis Lingkungan Kerja Fisik dan Non Fisik - Wijaya, Muhammad Dandy Arrizqi; Lestari, Dian (Universitas Batanghari, 2024)
An upsurge in the rate of teacher absences at Miftahul Huda Islamic Vocational School occurred during the academic year 2022-2023, necessitating an evaluation and enhancement of the school's infrastructure. Enhancing teacher job satisfaction yields numerous advantages for both teachers and students, particularly in the context of teaching and learning activities. The objective of this study is to examine endeavours to enhance teacher job happiness by concentrating on several elements of the work environment, encompassing both tangible and intangible factors. This research is characterised as quantitative and involved a total of 34 respondents. The sampling technique used was saturation sampling. The data gathering process involves the utilisation of library research and field research methodologies, along with data analysis methods such as descriptive and associative approaches. Data analysis involves the interpretation of the output table generated by the SPSS version 26 programme. This table is derived from previously processed data. The findings of this study indicate that both the tangible and intangible aspects of the work environment have a simultaneous impact on job satisfaction at Miftahul Huda Islamic Vocational School.